Challenges with accommodation among medical students of the University of Jaffna - Risafa, J.F.; Kayaline, S.; Arun, K.C.; Dissanayake, D.M.R.P.; Simra, E.F.; Kumar, R.; Ambalavanar, V. (University of Jaffna, 2024)
Introduction: Medical students face challenges in finding affordable accommodation located in proximity to the university and clinical training sites. This study describes the challenges faced by students of the Jaffna Medical Faculty in finding suitable accommodation, the key challenges they face with current accommodation and the socio- demographic and financial factors associated with these challenges. Methods: A university-based descriptive cross-sectional study was conducted at the Jaffna Medical Faculty among a study population of 812 students including the first through fourth years. Stratified random sampling was carried out to ensure proportionate representation across batches and genders. Data were collected through self- administered questionnaires and analysed with SPSS (v21). Standard descriptive statistics and the chi-square test was used in the analysis (critical level 0.05). Results: In total, 415 students participated (response rate 97.2%). Majority were females (59.8%), Tamil (53.7%) from outside Jaffna district (76.1%) and living in temporary accommodation (79.8%). Highest monthly expenses were on food and purified water (mean LKR 11810.78, median LKR 12000) and rent (mean LKR 4161.20, median LKR 5000). Among challenges in finding accommodation, the highest proportion reported difficulty finding accommodation near the faculty (28%). The three current challenges ranked number one by the highest proportion were food availability and water facilities (20.2%), safety and security (12.0%), and distance (8.4%). Among those paying rent, 27.7% reported rent was unaffordable. Ranking food availability and water facilities and safety and security as number one challenges were associated with sex, ethnicity, and district of residence, while ranking distance was associated with district of residence (p<0.05). Females, non-Jaffna and Muslim students were more likely to rank security first. Males (p=0.005), Sinhala students (p<0.001) and non-Jaffna students (p<0.001) were more likely to rank food and water as their first challenge; females (p=0.001), Muslim students (p<0.001) and non-Jaffna students (p<0.001) were more likely to rank security; and Jaffna students were more likely to rank distance (p=0.002). Conclusion: A substantial proportion of students from the Jaffna Medical Faculty face various problems related to accommodation, especially related to food and water, safety and security, distance and rent. As out-district students tend to be more affected, the university authorities could support incoming undergraduates to identify suitable accommodation.
Keywords: Student accommodation; Living expenses; Medical education; Socio- demographic factors; Jaffna